Online Public Access Catalogue: Factors Affecting Use E-Catalog - Farida Ardiani (IJID (International Journal on Informatics for Development), 2020)
Online Public Access Catalog (OPAC) is one of the e-catalog information technologies applied in libraries. OPAC is a library information retrieval system that can be accessed online. State Islamic University of Sunan Kalijaga Yogyakarta has been using OPAC since 2012 and OPAC users are increasing from year to year. An information system will be used by users if it suits their needs. The successful implementation of OPAC raises questions about the factors that influence this success. For this reason, this study aims to determine the factors that influence users to use OPAC. Structural Equation Modeling (SEM) is a multivariate statistical technique which is a combination of factor analysis and regression analysis (correlation) which aims to examine the relationships between variables in a model. Processing using SEM will be carried out to find the relationship between the variables to be tested, which variables are interconnected, and are there any unrelated variables. The results of processing the variables using SEM can show what variables attract users to use the e-catalog. Acceptance of information systems can be measured by several evaluation models that have been developed at this time. There are many evaluation models used to measure. Technology Acceptance Model (TAM) is the appropriate model to use for this study, because this study is about the acceptance of a system. In addition, several previous studies used by researchers as references also used TAM as their study method to assess user acceptance of a system. This study modifies TAM, which is used to determine user acceptance of an information system, by adding three exogenous variables, information quality, perceived enjoyment, and user interface. Results of this study proved that information quality, user interface, perceived usefulness, perceived ease of use, and behavioral intention to use, are all factors that influence the actual use of OPAC. Perceived enjoyment is a variable that cannot be proved affects the actual use of OPAC.